2020
DOI: 10.1177/2292550320928557
|View full text |Cite
|
Sign up to set email alerts
|

Management of Primary Necrotizing Fasciitis of the Breast: A Systematic Review

Abstract: Purpose: Necrotizing fasciitis (NF) is a life-threatening infection that involves spreading necrosis of the subcutaneous tissue and fascia that affects the extremities, abdominal wall, and perineum. Primary infection of the breast is a rare occurrence. Shah et al described the first case of primary breast NF and recommended radical “pseudotumor” excision and delayed skin closure months after resolution. Numerous other cases reported were successfully managed with different strategies. We aimed to summarize man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Treatment is mainly surgical and consisting of early debridement and radical excision of the infected tissue [ 11 ]. Through a review of literature, Marongiu found that mastectomy has been reported to be the most common surgical procedure [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is mainly surgical and consisting of early debridement and radical excision of the infected tissue [ 11 ]. Through a review of literature, Marongiu found that mastectomy has been reported to be the most common surgical procedure [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide variety of reconstruction options with split-thickness skin grafts being a common choice. Reconstruction of the defect can be completed within 2 weeks or once the patient is stable and free of infection 11 . Partial thickness skin grafts are indicated for large wounds and can survive in places with little vascularity such as breast tissue 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Split-thickness skin grafts (44.4%) and delayed primary closures (33.3%) were the most common methods of reconstruction. Septic shock at presentation was an independent risk factor for mortality (12.5%) in these patients (p<0.001) [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%